Bile acids as inflammatory mediators and modulators of intestinal permeability - Calzadilla, Nathan; Comiskey, Shane M.; Dudeja, Pradeep K.; Saksena, Seema; Gill, Ravinder K.; Alrefai, Waddah A. (Frontiers in Immunology, 2022)
Bile acids are critical for the digestion of lipids and fat-soluble vitamins; however, evidence continues to emerge supporting additional roles for bile acids as signaling molecules. After they are synthesized from cholesterol in the liver, primary bile acids are modified into secondary bile acids by gut flora contributing to a diverse pool and making the composition of bile acids highly sensitive to alterations in gut microbiota. Disturbances in bile acid homeostasis have been observed in patients with Inflammatory Bowel Diseases (IBD). In fact, a decrease in secondary bile acids was shown to occur because of IBD-associated dysbiosis. Further, the increase in luminal bile acids due to malabsorption in Crohn’s ileitis and ileal resection has been implicated in the induction of diarrhea and the exacerbation of inflammation. A causal link between bile acid signaling and intestinal inflammation has been recently suggested. With respect to potential mechanisms related to bile acids and IBD, several studies have provided strong evidence for direct effects of bile acids on intestinal permeability in porcine and rodent models as well as in humans. Interestingly, different bile acids were shown to exert distinct effects on the inflammatory response and intestinal permeability that require careful consideration. Such findings revealed a potential effect for changes in the relative abundance of different bile acids on the induction of inflammation by bile acids and the development of IBD. This review summarizes current knowledge about the roles for bile acids as inflammatory mediators and modulators of intestinal permeability mainly in the context of inflammatory bowel diseases.